STRATEGI PEMBELAJARAN KITAB KUNING MELALUI BANTUAN MATERI AL-MIFTAH LIL ULUM DI PONDOK PESANTREN SIDOGIRI PASURUAN - Sholihan (CENDEKIA: Jurnal Studi Keislaman, 2018)
Studying or reading Kitab Kuning, such as the hadith books or the Qur'anic commentaries is not an easy job. Need perseverance and other sciences such as Arabic, Nahwu, Shorrof, and so on are needed. Thus, if studied traditionally it will take quite a long time, even according to some circles it takes between 5 and 15 years to be able to read and understand it well. On this basis, the Sidogiri Islamic boarding school makes a Kitab Kuning learning method, which is easily understood and easily memorized by the santri with the hope that the students who live in Sidogiri in a short time can read and understand Kitab Kuning well. In 2010 the boarding school of Sidogiri succeeded in making yellow book learning method. This method is called Al-Miftah Lil Ulum. Initially this method was tested on 500 new santri. In a very short period of time around three months there were 350 students who could read and understand Kitab Kuning by using Al-Miftah Lil Ulum method. The results of this study indicate that: a) Yellow book learning planning using Al-Miftah Lil Ulum method is: (1) Formulating yellow book learning goals. (2) Determine the subject matter. (3) determine Kitab Kuning learning strategy. (4) Hold a placement test. (5) determine the allocation of school hours. b) Kitab Kuning learning process using the Al-Miftah Lil Ulum method consists of several stages: (1) preliminary stage. (2) core stage and (3) cover. c) Evaluation of yellow book learning using Al-Miftah Lil Ulum method using oral tests and written tests while the implementation of the tests is carried out in the learning process and outside the learning process.